The Impact of Contemporary Issues Jurisprudence (Fiqh al-Nawazil) on Islamic Feminism - Alwhash, Fatima Juma (Journal of Islamic Sciences, 2023)
With the passage of time and the emergence of new developments, challenges, and issues, it became necessary to determine the stance of Islamic jurisprudence on these issues. This study focuses on the impact of contemporary issues jurisprudence on the Islamic feminist movement in the West, particularly regarding some family issues present within the research.The study followed an inductive, analytical, and descriptive approach. The following results were:1.The concept of Islamic feminism involves disconnecting Muslim women from their beliefs and religious laws while solidifying Western feminist values, ideas, and principles.2.Emergence: Islamic feminism began to appear and spread in the 1990s.3.Reasons for its emergence: Among the main reasons for its emergence are migration to the West, openness, non-adherence to customs and traditions, and social and political changes.4.Gender reading: By presenting its texts and discussing them, one of the prominent terms within it is the term "gender," which refers to the differences between sexes. Gender discrimination is attributed to the social and cultural structure rather than the biological nature based on male and female sex. Masculinity and femininity are considered social and cultural constructs.5.The impact of contemporary issues jurisprudence on Islamic feminism and the Muslim woman’s identity. Contemporary issues jurisprudence addresses these issues in a way that aligns with the changing times and Islamic principles, without conflicting with the spirit of Sharia (objectives) to achieve public interests.
Keywords: Gender; Contemporary Issues Jurisprudence; Islamic Feminism; Sexual Repression